THE EFFECT OF SELLING PRICE AND HOUSEHOLD INCOME ON FARMERS' MOTIVATION IN PAPAYA FARMING IN WARINGINSARI VILLAGE, LANGENSARI DISTRICT, BANJAR CITY - Fitria Dewi, Dinda; Nuraini, Candra; Hartoyo, Tedi (Universitas Veteran Bangun Nusantara, 2025)
Papaya farming is one of the important sources of income for the community of Waringinsari Village. However, fluctuations in selling prices and household income often influence farmers’ motivation to maintain and develop their farming activities. The purpose of this study is to analyze the level of farmers’ motivation in conducting papaya farming in Waringinsari Village and to examine the influence of selling prices and household income on the motivation of papaya farmers in the village. The research was conducted from November 2024 to May 2025 using a survey method. Data were collected through questionnaires distributed to papaya farmers in Waringinsari Village, with a total sample of 32 respondents. The sampling technique employed was the census method. The data were analyzed using descriptive analysis and multiple linear regression. The results of the study indicate that farmers’ motivation in carrying out papaya farming falls into the high category, both intrinsic and extrinsic motivation. Simultaneously, selling prices and household income have a significant effect on farmers’ motivation in papaya farming in Waringinsari Village, Banjar City. Partially, both selling prices and household income also show a significant influence on farmers’ motivation in conducting papaya farming in Waringinsari. Keywords: Selling Price, Household Income, Motivation, Papaya, Waringinsari